2007
DOI: 10.1007/s00384-007-0367-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing electrode implantation in sacral nerve stimulation—an anatomical cadaver study controlled by a laparoscopic camera

Abstract: This study allows direct visualization during the placement of the needle and electrode, thus permitting accurate calculations of the best angle of approach during the surgical procedure in sacral nerve stimulation. These objective findings attempt to standardize this technique, which is often performed with the aid of intra-operative fluoroscopy but still leaving a lot to chance. These insertion angles should help to find more consistent and reproducible results and thus improved outcome in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…reported a median angle of needle entry into the S3 foramen of 69° (45–90) in the sagittal plane and Buchs et al . reported this to be 62.9 ± 3° (59–70). No gender‐related differences were noted (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…reported a median angle of needle entry into the S3 foramen of 69° (45–90) in the sagittal plane and Buchs et al . reported this to be 62.9 ± 3° (59–70). No gender‐related differences were noted (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…2 It is difficult to determine for sure if this small difference in reported S3 angles represents the soft tissue distortion commonly associated with supine storage of cadavers, the small population size of the cadaveric study, or a true nonparallel relationship of the skin and dorsal sacrum in live patients. A small cadaveric study (n = 5) recommended a needle insertion angle of approximately 60 degrees relative to the skin and found that acute angles (near 50 degrees) were more likely to be malpositioned.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some researchers challenge the currently dominant concept concerning stimulation of the S3 nerve root, suggesting that in some patients S4 stimulation may be used as either salvage or first option, as it might be associated with lesser risk of leg pain whilst still achieving sufficient pelvic floor contractions and perianal sensations 16. Novel approaches in SNM, such as pudendal nerve stimulation, suggest that S2 stimulation is also associated with good clinical outcomes 21, 22 …”
Section: Prognostic Factorsmentioning
confidence: 99%